INOVASI PELAYANAN KELOMPOK PEDAGANG CANANG DI LINGKUNGAN KARANG JASI KOTA MATARAM - Wiguna Murti, I Wayan Indra (Waisya : Jurnal Ekonomi Hindu, 2024)
Post covid 19 pandemic that hit the world made sales decline, especially the Canang Traders Group in the Karang Jasi Neighborhood, Mataram City. This research focuses on three things, namely: (1) the sales trend of the canang trader group in the Karang Jasi Neighborhood, Mataram City, (2) the form of service innovation of the canang trader group in increasing sales, (3) the supporting and inhibiting factors of the canang trader group in innovating services. The research methodology uses descriptive with data collection techniques using observation, interviews, and documentation techniques. the results of this study show, the form of service innovation where canang traders provide services by delivering orders to customers' homes. supporting factors in this study can be known, namely to meet needs such as demands for daily living expenses, school fees, the desire to develop a business, the desire to get more profit, then the obstacles are lack of knowledge in using telephones and WhatsApp, capital, many competitors.